2008
DOI: 10.1016/j.joen.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mineral Trioxide Aggregate on Adaptive Immune Responses to Endodontic Pathogens in Mice

Abstract: This study assessed the influence of mineral trioxide aggregate (MTA) on adaptive immune responses. BALB/c mice were immunized with heat-killed Fusobacterium nucleatum (Fn) in MTA or other control adjuvants, and serum IgG responses to Fn were measured. Either Fn-or Peptostreptococcus anaerobius (Pa)-reactive memory T cells (Tm) were pre-incubated in vitro with/ without MTA and restimulated with Fn or Pa. Tm proliferation and cytokine production were assessed. Compared to control groups, IgG-antibody responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
6
18
0
1
Order By: Relevance
“…MTA induces inflammation via a transcription factor nuclear factor-kappa B signaling system (25). MTA up-regulates the adaptive humoral immune response (26). Accorinte et al (27) showed that although pulp healing with calcium hydroxide is slower than with MTA, both materials are good for pulp capping in human teeth.…”
Section: Discussionmentioning
confidence: 99%
“…MTA induces inflammation via a transcription factor nuclear factor-kappa B signaling system (25). MTA up-regulates the adaptive humoral immune response (26). Accorinte et al (27) showed that although pulp healing with calcium hydroxide is slower than with MTA, both materials are good for pulp capping in human teeth.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the worse results of groups that received mycophenolate mofetil, sirolimus, and cyclosporine A. MTA is biocompatible material that does not interfere with the normal reparative mechanism for pulp healing. Some authors (7,41) stated that it might promote healing and allow cytokine release. Immunosuppressive drugs (mycophenolate mofetil, sirolimus, cyclosporine A) might interfere with repair mechanism through their negative effect on cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6j mice (8-week-old males, n=5/group) were immunized with or without heat-killed Pasteurella pneumotropica (P. pneumotropica) or Enterococcus saccharolyticus ( E. saccharolyticus ) (3×10 8 CFU/mouse, subcutaneous [s.c.] injection) in Freund’s adjuvant following the method previously published (17). Four days after booster injection (s.c.) of bacteria in PBS, lymph nodes and blood serum were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…Sera isolated from mice were reacted to heat-killed bacteria (10 7 /ml) coated on ELISA plates, and the reacted serum IgG antibodies were measured by ELISA (17). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation